KESANTUNAN TINDAK TUTUR EKSPRESIF DALAM KOLOM KOMENTAR YOUTUBE AKUN ROCKY GERUNG - Mellani Nurritha; Fatmawati - (Universitas Muria Kudus, 2026)
This study was motivated by the rapid development of information and communication technology, which has significantly transformed the way people interact. One platform that provides a space for interaction through user comments is YouTube. The objective of this study is to examine the politeness of expressive speech acts used in the comment section of Rocky Gerung's YouTube channel. This research employs Leech’s politeness theory and adopts the nineteen forms of expressive speech acts proposed by Nabila Syafarendra. A qualitative approach was applied in this study. The data consisted of expressive speech acts containing politeness principles, while the data source was comments posted on videos uploaded to Rocky Gerung's YouTube channel. Data were collected through documentation, reading, and observation techniques. The data were analyzed using the content analysis method based on Burhan Bungin's (2008) approach. The findings reveal eleven forms of expressive speech acts with varying degrees of politeness, namely praising, thanking, criticizing, interrupting, blaming, expressing sympathy, accusing, insulting, degrading, supporting, and expressing surprise. Criticizing speech acts may be considered polite or impolite depending on the choice of words and the manner in which they are conveyed. Meanwhile, interrupting, blaming, accusing, insulting, and degrading speech acts tend to violate politeness principles because they contain elements of belittling, attacking, or showing disrespect, thereby conflicting with the tact maxim, approbation maxim, and agreement maxim. Furthermore, speech acts expressing surprise can be categorized as polite when conveyed appropriately and without offending others, but they may become impolite when accompanied by sarcastic or derogatory expressions.